Nitrogen doses and splitting in top dressing in the production and macronutrient content in fruits of zucchini - Tavares, Ana Emília Barbosa (2023)
Nitrogen fertilization in cucurbits must be splitted, one part being supplied before planting and the rest applied in top dressing. However, there is a lack of research about this splitting throughout the cycle. The objective of this study was to evaluate the effect of nitrogen doses and splitting of this fertilization in top dressing on production and macronutrient content in fruits of zucchini. Two experiments were carried out, with thirteen treatments, in the factorial scheme 4x3+1, with four nitrogen doses in top dressing (62.5, 125.0, 187.5, 250.0 kg ha-1 of N), three splitting forms (1/6+1/3+1/2; 1/4+1/2+1/4; 1/3+1/3+1/3 of total dose in each application) and one treatment without fertilization in top dressing (control = dose zero), with four replicates. Experiment 1 and 2 were conducted in 2014 and 2015, respectively. Total and commercial fruit production (g), total and commercial fruit number per plant, length, diameter and average commercial fruit weight were evaluated. Only in experiment 2 the macronutrient content in the fruits were evaluated. In experiment 1, the 1/4+1/2+1/4 splitting provided greater number of total and commercial fruits per plant. In experiment 2, the increasing of the doses in the 1/6+1/3+1/2 and 1/3+1/3+1/3 splitting resulted in a linear increase in total and commercial fruit production. The decreasing order of macronutrient content in fruits was K>N>P>Ca>Mg>S.